Evaluating the Design of Behavior Change Interventions: A Case Study o f Rhino Horn in Vietnam - Olmedo, Alegría; Sharif, Vian; Milner-Gulland, E. J. (Conservation Letters, 2018)
Behavioral change interventions are increasingly widely used in conser vation. Several projects addressing rhino horn consumption were recent ly launched in Vietnam. We used key informant interviews, document ana lysis, and marketing theory to explore their strategies for interventi on design, implementation, monitoring, and evaluation. We developed a framework to evaluate whether they followed best practice and identify implementation challenges. Interventions could make greater use of ke y project design steps, including basing interventions on robust resea rch to understand the behavior in question, identifying the target aud ience whose behavior interventions aim to change, and developing measu res that can provide reliable evidence of success or not. Challenges i nclude the need for law enforcement to complement campaigns; improving cooperation between NGOs; and clearly defining aims of demand-reducti on initiatives. Using best practice from other fields and considering demand reduction within the wider context of wildlife, trade policy wi ll help address these challenges.
Keywords: Awareness; Ilegal wildlife trade; Project design; demand reduction; social marketing